2007
DOI: 10.1159/000099020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Single High Dose of Cisplatin on the Melanocytes of the Stria Vascularis in the Guinea Pig

Abstract: The antineoplastic drug cisplatin is known to cause a reduction in endocochlear potential. The hypothesis to be tested was whether a single high dose of cisplatin affects the melanocytes by altering the expression of melanin. Pigmented guinea pigs received a bolus injection of cisplatin (8 mg/kg as a 15-second intravenous infusion). Auditory brainstem response (ABR) thresholds and morphological analysis of the hair cells and the stria vascularis were made 96 h after injection. ABR thresholds were elevated (15–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 60 publications
1
32
0
Order By: Relevance
“…Younger age as a risk factor has been observed in previous studies (1,(8)(9)(10)26), but was not evident in our analysis. Aguilar-Markulis et al (27) suggested that adults receiving cisplatin may be vulnerable to additive damage from previous or concurrent use of other potentially ototoxic drugs, in accordance with other studies (28,29). Simon et al (30) also observed no association between age and risk of developing hearing impairment, similar to our results.…”
Section: Discussionsupporting
confidence: 92%
“…Younger age as a risk factor has been observed in previous studies (1,(8)(9)(10)26), but was not evident in our analysis. Aguilar-Markulis et al (27) suggested that adults receiving cisplatin may be vulnerable to additive damage from previous or concurrent use of other potentially ototoxic drugs, in accordance with other studies (28,29). Simon et al (30) also observed no association between age and risk of developing hearing impairment, similar to our results.…”
Section: Discussionsupporting
confidence: 92%
“…In melanocytes, a single high dose of Cisplatin was shown to reduce the production of melanin but caused no apoptosis 443 . Melanocytes were also seen to be less susceptible to cell death caused by Etoposide, Cisplatin, Paclitaxel, or the MEK inhibitor PD184352, than melanoma cells 306,444,446 .…”
Section: Chapter 6 Conclusionmentioning
confidence: 99%
“…As a positive control for proteasomal inhibition by MG132 and to determine the optimal dose of the inhibitor, we assessed the expression of Mcl-1 and p-IB, two proteins known to be targeted for degradation by the proteasome 39,443 . We observed that the levels of Mcl-1 and p-IB accumulated with the doses of 10g/ml and 2g/ml, but not at 50g/ml, possibly due to toxicity of the inhibitor at this high dose.…”
Section: Degradation Of the Bfl-1 Protein In Melanoma Cellsmentioning
confidence: 99%
“…There is some experimental evidence that morphological injury to the supporting cells precede injury to the OHCs (Laurell and Bagger-Sjöbäck 1991a , b ;Estrem et al 1981 ;Ramirez-Camacho et al 2004 ). Evidence for involvement of the strial vascular architecture in the toxic processes that is associated with cisplatin injury also has been found in some human and experimental studies (Tange 1987 ;Sluyter et al 2003 ;Komune et al 1981 ;Laurell et al 2007 ). A temporary or permanent lesion to the stria vascularis corresponded to the decline of the endocochlear potential observed in some electrophysiological studies on cisplatin ototoxicity Komune et al 1981 ;Laurell and Engström 1989a , b ).…”
Section: Morphological Changesmentioning
confidence: 84%